Disease Prevention Not Decolonization: A Model for Fecal Microbiota Transplantation in Patients Colonized With Multidrug-resistant Organisms. (18th July 2020) - Ghani, Rohma; Mullish, Benjamin H; McDonald, Julie A K; Ghazy, Anan; Williams, Horace R T; Brannigan, Eimear T; Mookerjee, Siddharth; Satta, Giovanni; Gilchrist, Mark; Duncan, Neill; Corbett, Richard; Innes, Andrew J; et al.
Abstract: Fecal microbiota transplantation (FMT) yields variable intestinal decolonization results for multidrug-resistant organisms (MDROs). This study showed significant reductions in antibiotic duration, bacteremia, and length of stay in 20 patients colonized/infected with MDRO receiving FMT (compared with pre-FMT history, and a matched group not receiving FMT), despite modest decolonization rates.